Estimating phosphorus delivery from land to water in headwater catchments using a fuzzy decision tree approach. (5th March 2013) - Scholefield, P.; Heathwaite, A. L.; Brazier, R. E.; Page, T.; Schärer, M.; Beven, K.; Hodgkinson, R.; Withers, P.; Walling, D.; Haygarth, P. M.
Abstract: The pathway that delivers mobilized phosphorus (P) from source to surface water is conceptually complex. Firstly, P mobilization itself, either through mechanical disturbance of the soil or through chemical dissolution or weathering, is difficult to measure in situ ; secondly, the annual flow‐weighted mean concentration of P is a difficult metric to gather. Summarizing these pathway processes as the ratio of the delivered P to the mobilized fraction of P assists in the quantification and assessment of the P transfer continuum. The proportion of this mobilized P that is subsequently delivered to the watercourse is also difficult to quantify. A range of P models already exist that aim to predict P mobilization and delivery. Reasonable estimates can be made for the outputs of P from a plot or small catchment over a series of events. Current models mainly rely on empirical data or expert judgment to derive appropriate coefficients of P transfer and delivery. This paper describes the research designed to evaluate the range of delivery coefficients from headwater catchments that might be anticipated for different land‐use regions across the UK. These coefficients were evaluated within a fuzzy decision tree framework. The delivery coefficients used in this study covered a broad range of possible values from all available data describing P fluxes from headwater catchments in the UK. The results of this work indicate that delivery coefficients are a useful way of summarizing the mobilization behaviour of a headwater catchment. Mean delivery coefficients above unity were present in four of 18 catchments, indicating higher than average delivery, probably due to intensive agricultural management practices. This first use of a fuzzy or uncertain approach to model P delivery in the UK has generated potentially promising results, and a methodology has been developed for producing delivery coefficients using sparse data, which may be applicable to other headwater catchments.